Автоматизированная система электростимуляции точек акупунктуры стопы - Гунбин, Михаил Владимирович; Дудник, Алексей Валентинович; Ивашко, А. А.; Вуялкина, С. А.; Ярмола, Е. А. (НТУ "ХПИ", 2007)
У статті описуються виникнення і методи рефлексотерапії, порівнюються західний та східний підхіди до медицини. Розглядається вплив електромагнітотерапії та імпульсної терапії на організм людини. Проводиться аналіз точок акупунктури стопи, а також приводиться їх зв’язок з різними захворюваннями. Розроблено метод автоматизованого визначення координат точок акупунктури та електроімпульсного впливу на них.

In this paper methods and apparatus of reflexotherapy are described, western and eastern approaches to medicine are compared. Influence of an electromagnetotherapy and pulse therapy on the human organism is considered. The analysis of acupuncture points of the foot is spent, and also their interrelation with various diseases is resulted. Method of automatic selection and electrical influence on of acupuncture points has been developed.
Keywords: медицина; методы лечения; рефлексотерапия; морфология; биологические ритмы; самовосстановление